Management of hypertensive patient in clinical pharmaceutical care: A case report (Research, Society and Development, 2021)
Pharmaceutical services consist of pharmacotherapeutic monitoring in the identification and resolution of drug-related problems (DRPs) through interventions. Monitoring hypertensive patients is essential, as hypertension is considered one of the main risk factors that contribute to mortality from cardiovascular diseases. In this report, we discuss cardiovascular risk factors in hypertensive patients and the pharmacological and non-pharmacological interventions performed to resolve the present DRPs. This is a descriptive study, of the case report type of a patient in a pharmaceutical consultation at the University Pharmacy of the Federal University of Bahia, from October 2019 to April 2020 (CEP nº 2.578.262). The questionnaires and interventions were based on the document "Pharmaceutical Care in Primary Care: notebook 2", from the Ministry of Health. Case report: Female patient, 72 years old, diagnosed with hypertension for years, presents comorbidities such as dyslipidemia, in addition to style sedentary lifestyle that, mutually, configure themselves as important cardiovascular risk factors. She practiced self-medication and had several adherence DRPs. Of the pharmaceutical interventions performed, they included: health education regarding the rational use of medications (RUM), adjustments to correct the DRPs, encouragement of healthy eating and the practice of physical exercise. In view of the elaboration of pharmaceutical intervention plans, adopting drug and non-drug therapies, it was possible to reduce blood pressure levels, RUM and improve the patient's quality of life.